Seismic Fragility Analysis of Self-Anchored Suspension Bridge Considering Damping Effect. (16th August 2022) - Zhou, Xiangong; Cao, Lei; Han, Heng; Zheng, Xiaobo; Zhang, Hanhao; Zhang, Zhiqing
Abstract : The self-anchored suspension bridge is a kind of the flexible and redundant structural system. For this type of bridge, the current code only gives the overall seismic design principle, and there is little research on seismic fragility in the existing literature. Taking the three-tower self-anchored suspension bridge as the research object, the finite-element dynamic models with and without damping are established, respectively. Based on the strong earthquake database of PEER (Pacific Earthquake Engineering Research), 10 ground motion records are selected, and the seismic fragility curves of piers, bearings, towers, and slings are established by using the incremental dynamic analysis (IDA) method. The fragility curves of the bridge system were established by first-order reliability theory. In this study, the damage probability of bridge components under a seismic wave is studied. The results show that the damage exceedance probability of the damped connection system is reduced compared with the undamped fully floating structure system under the action of seismic waves. The damper device makes the seismic performance of the structure significantly improved, and the reduction effect of the damper device on high-intensity earthquakes is more obvious than that on low-intensity earthquakes.